Effect of Different Forms of Fluoride Application on Surface Roughness of Rhodium-Coated NiTi Orthodontic Wires: A Clinical Trial - Masoud Khanloghi; Sedigheh Sheikhzadeh; Soraya Khafri; Maysam Mirzaie (Tehran University of Medical Sciences, 2023)
Objectives: This study aimed to assess the effect of different forms of fluoride application on surface roughness of rhodium-coated nickel-titanium (NiTi) orthodontic wires. Materials and Methods: This randomized clinical trial was conducted on 15 patients randomly divided into three groups: toothbrush with Oral-B toothpaste only, Oral-B toothpaste, and daily mouthwash, Oral-B toothpaste, and sodium fluoride gel. The surface roughness indices of orthodontic wires including arithmetic mean height (Sa), root mean square height, root mean square gradient, developed interfacial area ratio (Sdr) and maximum surface height were measured by atomic force microscopy at baseline and after 6 weeks of application in the patients' mouths. Data were analyzed by paired t-test, ANOVA, Games-Howell, and Tukey-HSD tests (P<0.05). Results: All surface roughness parameters in all three groups showed a significant increase after intervention, except for Sa in the toothpaste-only group (P=0.057) and Sdr in the sodium fluoride gel group (P=0.064). Conclusion: The surface roughness of rhodium-coated NiTi orthodontic wires increases following the use of different forms of fluoride.